Enhanced Raman Scattering by Molecular Nanoaggregates - Daniel L. Akins (Nanomaterials and Nanotechnology)
The formation of a molecular aggregate in a confined, nanodimensioned region of space leads to what might be termed a ‘molecular nanoaggregate’. The present review deals with a theoretical formulation termed ‘aggregation-enhanced Raman scattering’ (AERS), and its use in discussion of relative Raman band intensities and selection rules for nanoaggregates. AERs represents a concept for discussion of nanoaggregates that is different from those provided by resonance Raman scattering, surface-enhanced Raman scattering and Mie scattering, all of which ignore the impact of aggregation of molecules on Raman scattering. Beyond the theoretical formulation behind the AERS phenomenon, also outlined in this review are representative samples of the publications of other authors and researchers using AERS to provide explanations for experimental findings. In addition to clarifying issues regarding the use of nanocomposites involving aggregated molecules, it is found that increasing use of AERS concepts is being made to rationalize Raman spectral observations in a range of other disciplines that fall in both the physical sciences and the medical fields.